Pengaruh Hujan terhadap Perubahan Elevasi Muka Air Tanah pada Model Unit Resapan dengan Media Tanah Pasir - Wahyunika Sari, Burhan Barid , (Universitas Muhammadiyah Yogyakarta, 2013)
This study aimed to determine changes in ground water level against time to recharge the unit models with medium sand soil in cloudburst conditions, to determine the effect of changes in humidity land in heavy rain conditions and for the efficiency of the model unit catchment .. By using the model infiltration unit made from box 170x170x200 cm3 and infiltration well with dimensions of 30x30x100 cm3 filled with 90 cm thick layer of sandy soil . The results showed that changes in ground water level is 18.8 % , 22.4 % and 24 % for the test I, II, III , respectively .. Soil moisture for the test I ran to saturation at 110 minutes , while for II and III trials in the 90th minute . Unit efficiency filtration models in improving the soil surface water is 3.6 % . This suggests that these filtration units of the model can reduce surface water runoff and increasing groundwater levels.Â